CHOICE OF TERMS FOR SURGICAL TREATMENT OF UNSTABLE PELVIC RING IN VICTIMS WITH POLYTRAUMA BASED ON ANATOMY-FUNCTIONAL ASSESSMENT OF THE TRAUMA SEVERITY - Burluka, V.V.; Ankin, N.L.; Denisenko, V.N.; Maksymenko, M.A.; Shepitko, K.V. (World of Medicine and Biology, 2020)
The purpose of the work was to improve the results in patients with unstable pelvic injuries in polytrauma. The study of integral rheography indices of the body was performed and some laboratory blood parameters in 137 patients with unstable pelvic injuries in polytrauma (UPIP) were studied. The victims had unstable pelvic injuries, namely types B and C according to the international classification of AO (M. Tile, 1995). Rotationally unstable fractures (type B) were observed in 101 (73.72%) cases, vertically unstable (type C) - in 36 (26.28%). It has been scientifically substantiated that the severity of anatomical injuries and the prediction of the condition for patients with UPIP upon admission should be more informatively assessed using the ATS scale (statistical significance - 89.29%). Surgical interventions on the pelvic bones in case of mild and severe trauma are possible from the 5th-7th days of traumatic disease, with extremely severe trauma - from 10-14 days of TC with a favorable prognosis, which was determined taking into account the indices of integral body rheography.